Protective role of adrenomedullin in burn-induced remote organ damage in the rat - ERCAN, FERİHA (ELSEVIER SCIENCE BV, 2008)
Clinical and experimental research findings suggest that a local burn insult produces oxidant-induced organ changes as evidenced by increased lipid peroxidation in lung, liver and gut. Adrenomedullin (AM), a potent vasodilator, was originally isolated from pheochromocytoma cells, and has been identified in other tissues. In this study, we investigated the potential role of AM in burn-induced remote organ damage in rats. Sprague-Dawley rats (250-300 g) were treated with either AM (100 ng/kg, subcutaneously) or saline 10 min before burn insult which covers 30% of total body surface area and were decapitated 24 It after the burn insult. Trunk blood was collected and analyzed for liver and kidney functions and for determination of TNF-alpha levels. The liver, lung and kidney samples were taken for histologic evaluation and for measurement of malondialdehyde (MDA) level, myeloperoxidase (MPO) activity and chemiluminescence levels. The data revealed that AM treatment resulted in a significant protection in tissues tested against burn injury via suppression of lipid peroxidation, tissue neutrophil infiltration, oxidant generation and via decreasing circulating levels of the pro-inflammatory cytokine TNF-alpha. AM treatment was also effective in attenuating hepatic and kidney dysfunction due to burn injury, suggesting that peripherally AM administration may protect the tissues against burn-induced injury. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: adrenomedullin; burn; kidney; liver; lung; rat; AUREUS ALPHA-TOXIN; THERMAL-INJURY; HYPOTENSIVE PEPTIDE; BACTERIAL TRANSLOCATION; ISCHEMIA-REPERFUSION; LIPID-PEROXIDATION; BINDING PROTEIN-1; OXIDATIVE STRESS; INFLAMMATION; EXPRESSION